The Transcriptomic Landscape of Age-Induced Changes in Human Visceral Fat and the Predicted Omentum-Liver Connectome in Males - Moraes, Diogo de [UNESP]; Mousovich-Neto, Felippe; Cury, Sarah Santiloni [UNESP]; Oliveira, Jakeline [UNESP]; Souza, Jeferson dos Santos [UNESP]; Freire, Paula Paccielli [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Mori, Marcelo Alves da Silva; Fernandez, Geysson Javier; Carvalho, Robson Francisco [UNESP] (My University, 2023)
Aging causes alterations in body composition. Specifically, visceral fat mass increases with age and is associated with age-related diseases. The pathogenic potential of visceral fat accumulation has been associated with its anatomical location and metabolic activity. Visceral fat may control systemic metabolism by secreting molecules that act in distal tissues, mainly the liver, through the portal vein. Currently, little is known about age-related changes in visceral fat in humans. Aiming to identify molecular and cellular changes occurring with aging in the visceral fat of humans, we analyzed publicly available transcriptomic data of 355 omentum samples from the Genotype-Tissue Expression portal (GTEx) of 20–79-year-old males and females. We identified the functional enrichment of genes associated with aging, inferred age-related changes in visceral fat cellularity by deconvolution analysis, profiled the senescence-associated secretory phenotype of visceral adipose tissue, and predicted the connectivity of the age-induced visceral fat secretome with the liver. We demonstrate that age induces alterations in visceral fat cellularity, synchronous to changes in metabolic pathways and a shift toward a pro-inflammatory secretory phenotype. Furthermore, our approach identified candidates such as ADIPOQ-ADIPOR1/ADIPOR2, FCN2-LPR1, and TF-TFR2 to mediate visceral fat-liver crosstalk in the context of aging. These findings cast light on how alterations in visceral fat with aging contribute to liver dysfunction and age-related disease etiology.
Keywords: age-related diseases; aging; fat-liver crosstalk; obesity; visceral adipose tissue